Fact-checking Literacy of Covid-19 Infodemic on Social Media in Indonesia - Dedeh Fardiah; Ferry Darmawan; Rini Rinawati (Universitas Muhammadiyah Yogyakarta, 2022)
The massive spread of information about COVID-19 hoaxes since 2020 is a problem that any country, including Indonesia, must face. In anticipation of this, the West Java government conducted a fact-checking process using multiplatform Instagram @jabarsaberhoaks. This study aims to identify the fact-checking process that has been carried out by @jabarsaberhoaks accounts using the content analysis method of identifying 334 posts about COVID-19 hoaxes during 2020. The results showed that @jabarsaberhoaks conducted the fact-check by finding data from various hoax themes by checking official sources such as media, authorized agencies, and expert sources nationally and internationally. A note of correction of the clarification results from COVID-19 was published on Instagram. This research finding necessitates stakeholders intensify their campaigns and educate the community on COVID-19 information literacy to understand and respond to the COVID-19 phenomenon adequately.